2016
DOI: 10.1002/mrm.26207
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D magnetic resonance elastography: Comparison with dynamic mechanical analysis

Abstract: PurposeMagnetic resonance elastography (MRE) is a rapidly growing noninvasive imaging technique for measuring tissue mechanical properties in vivo. Previous studies have compared two‐dimensional MRE measurements with material properties from dynamic mechanical analysis (DMA) devices that were limited in frequency range. Advanced DMA technology now allows broad frequency range testing, and three‐dimensional (3D) MRE is increasingly common. The purpose of this study was to compare 3D MRE stiffness measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…They reported an ICC of 0.99 for the magnitude of the complex shear modulus between DI-MRE of large homogeneous phantoms and DMA using 8 polyvinyl chloride samples. [45] In our study, the NLI-MRE and DMA techniques also revealed consistency with an ICC of 0.72 between the storage modulus of the silicone, agar, and tofu samples and the heterogeneous phantoms.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…They reported an ICC of 0.99 for the magnitude of the complex shear modulus between DI-MRE of large homogeneous phantoms and DMA using 8 polyvinyl chloride samples. [45] In our study, the NLI-MRE and DMA techniques also revealed consistency with an ICC of 0.72 between the storage modulus of the silicone, agar, and tofu samples and the heterogeneous phantoms.…”
Section: Discussionsupporting
confidence: 77%
“…[45]. Intraclass correlation coefficient (ICC) was also computed to measure the consistency between the NLI estimates and DMA measurements with a one-way random effects model.…”
Section: Methodsmentioning
confidence: 99%
“…1 of Arunachalam et al 41 ) was 8.1 in the soft material, whereas N was between 17 and 25 for in vivo data. Because N and SNR have adverse effects on the apparent SWS, the ratio N / SNR is plotted on the x‐axis. Dependent on the ratio N / SNR , the dispersion‐by‐inversion bias can cause either an overshoot or undershoot of values, both enhanced by second‐order finite derivative methods such as AHI.…”
Section: Resultsmentioning
confidence: 99%
“…The different ROI sizes used in the five MRE sequences may have an effect on the stability of the stiffness measurements because of the liver parenchyma stiffness heterogeneity often observed in MRE elastograms. While previous work has established the validity of 3D MRE when compared to mechanical testing of phantoms, it has also been observed that 3D hepatic MRE stiffness values can be lower than 2D MRE values, while having comparable diagnostic accuracy and fewer failures …”
Section: Discussionmentioning
confidence: 98%